2005
DOI: 10.1007/s00204-005-0651-y
|View full text |Cite
|
Sign up to set email alerts
|

Platelet-activating factor (PAF) involvement in acetaminophen-induced liver toxicity and regeneration

Abstract: Acetaminophen-induced toxicity has been attributed to cytochrome P-450-generated metabolites, which covalently modify target proteins. However, the mechanism of liver injury pathogenesis needs to be further elucidated. Platelet-activating factor (PAF) is one of the mediators involved in inflammatory tissue alterations associated with acute liver failure. In this study, alterations in blood PAF levels and the serum activity of PAF-acetylhydrolase (PAF-AH) were investigated over the time course of liver injury a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0
2

Year Published

2006
2006
2012
2012

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 42 publications
2
17
0
2
Order By: Relevance
“…This hepatotoxin produces a dose-related centrilobular necrosis in the liver (3,17). Grypioti et al (18) reported that the elevated serum levels of hepatic AST, ALT (indicative of necrosis) and ALP (indicative of cholestasis) activities are in good agreement with the fi rst wave of liver injury observed between 20 and 40 h, and are due to the direct action of APAP on hepatocytes.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…This hepatotoxin produces a dose-related centrilobular necrosis in the liver (3,17). Grypioti et al (18) reported that the elevated serum levels of hepatic AST, ALT (indicative of necrosis) and ALP (indicative of cholestasis) activities are in good agreement with the fi rst wave of liver injury observed between 20 and 40 h, and are due to the direct action of APAP on hepatocytes.…”
Section: Discussionsupporting
confidence: 65%
“…Grypioti et al (18) reported that ALT, AST and ALP values increased and that the liver changed histopathologically (grade of infl ammation and apoptosis). They observed in their rat model that hepatic injury was generated with a toxic dose (3.5 g/ kg) of acetaminophen.…”
Section: Discussionmentioning
confidence: 99%
“…However, the effect of rPAF-AH on liver injury caused by APAP has not been determined. We have previously reported that PAF was increased at almost the same time for all biochemical parameters (AST, ALT, and ALP) indicative of liver injury in APAP-treated rats (21). This correlation could be explained by the fact that PAF is considered to be one of the main mediators that cause organ injuries followed by necrosis [44][45][46].…”
Section: Discussionmentioning
confidence: 88%
“…In a previous study, we demonstrated that PAF is involved in the pathogenesis of acute liver injury and in augmented compensatory liver tissue repair post-APAP treatment [21]. In the present study we evaluated whether enhanced degradation of PAF by increasing PAF-AH levels has any influence on tissue recovery after APAP poisoning.…”
Section: Introductionmentioning
confidence: 85%
“…PAF has neurological toxicity [8] . It is also involved in etiopathogenesis of type-1 diabetes [9] and liver tissue repair post-acetaminophen treatment [10] .…”
Section: Introductionmentioning
confidence: 99%